1974
DOI: 10.1126/science.184.4139.911
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Correlation of Brightness Enhancement and Transients in the Nervous System

Abstract: Short light flashes can appear brighter than longer flashes. This brightness enhancement has often been attributed to neural transients occurring shortly after stimulus onset. This attribution assumes an equivalence between the totality of the response to a stimulus of a given duration and the instantaneous response at a given time after stimulus onset. Recordings from Limulus photoreceptors indicate that this attribution is an example of illusory correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…Plotting a transient visual response produces a curve that resembles a Broca-Sulzer curve. Yet, as Wasserman and Kong (1974) made clear, the Broca-Sulzer effect cannot be the result of transient visual activity. In a Broca-Sulzer experiment the observer does not see a patch of light growing and then dimming over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plotting a transient visual response produces a curve that resembles a Broca-Sulzer curve. Yet, as Wasserman and Kong (1974) made clear, the Broca-Sulzer effect cannot be the result of transient visual activity. In a Broca-Sulzer experiment the observer does not see a patch of light growing and then dimming over time.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the net output n is a function of time, while the Broca-Sulzer function represents brightness that changes with duration τ (Berman & Stewart, 1978a, 1978b, 1979Wasserman & Kong, 1974).…”
Section: A Formal Modelmentioning
confidence: 99%
“…We empirically demonstrated, in intracellular recordings from single photoreceptor cells (Wasserman & Kong, 1974), that these two different characterizations of the exact same responses yield completely different outcomes: increasing the duration of the stimulus ensemble produces a monotone increase in the amplitude of the set of neural responses, whereas the amplitude of the neural response to a single stimulus first increases and then decreases as time after stimulus onset increases.…”
mentioning
confidence: 98%
“…Thecomparison of brain with behavior may be adversely affected by an illusory correlation between time and duration (Wasserman & Kong, 1974). This time/duration illusory correlation is extremely potent, and it has a tendency to recur even though it has been authoritatively recognized (see Uttal, 1981, pp.…”
mentioning
confidence: 99%
“…One problem with this analysis is that physiological data represent neural activity as a function of time generated by a flash of a given duration, whereas psychophysical data reflect changes in brightness as a function of duration (Wasserman & Kong, 1974 change in a nonmonotonic fashion with duration. However, Wasserman and Kong (1974) showed that the initial transient measured electrophysiologically in the limulus, changed monotonically with duration.…”
mentioning
confidence: 99%